Habibie, dari Pare-Pare lewat Aachen dan tulisan-tulisan lain - Habibie, B. J. (Bacharuddin Jusuf), 1936- (Humas BPP Teknologi, 1982)
Collection of articles and interviews with B.J. Habibie, Minister of State for Research and Technology and head of P.T. Nurtanio, Indonesia's aerospace industry; previously published in Berita Yudha daily, Eksekutif, Kaleidoscope, Interavia, and Flight International magazines.